Pedagogy for Teaching Fire Safety through Design-Based Immersion of the National Building Code 2016 with Feedback from Students of Undergraduate Architecture - Raja Singh (The Scientific World Journal, 2023)
This study is based on the feedback from 3rd-year architectural undergraduate students at a leading architectural education college in India. An undergraduate degree in architecture in India leads to a professional license to practice as an architect in India. Fire safety is also a component of the architectural curriculum, but there are concerns worldwide that architecture colleges may somehow not give the impetus fire safety education may require. A studio-based, immersive pedagogy was created to make fire safety more relevant and easy to grasp for architecture students. This method used integrating the interventions from the country’s fire code into the design using students’ self-created design problems, with which they were familiar. This design-based immersive integration of the National Building Code 2016 and its fire provisions were tested in this study. The detailed course pedagogical structure has been presented. The study was tested using feedback from the students at the end of the semester using an 11-part questionnaire which 32 students answered in an anonymous mode. The results show an overall positive response where the students prefer a design-based integrated fire safety curriculum which introduces fire codes to the students in the applied format. This study paves the way for more replications of the studio design-based integration of fire codes into the curricula of architecture colleges. Further studies will require this technique to undergo further testing by involving practitioners who have undergone this pedagogy and testing the same in building projects.